Attainment's managing threatening confrontations [videorecording]. - White, Paul; Reily, Rich; Schultz, Jeff (Attainment Co., 2004)
"Years of experience working with people who exhibit challenging behaviors helped Paul White create a five-stage framework for professionals to manage threatening confrontations. For frontline staff in the fields of developmental disabilities and mental illness who deal with potentially explosive situations"--Container.